The effects of a 12-week moderate-intensity continuous training intervention on depression, anxiety, and stress in sedentary female college students: a focus on negative emotion regulation - Zeng, Quanwen; Zhang, Yong; Li, Huimin; Yuan, Jin; Feng, Dan; Zhu, Gendi (Frontiers in Psychology, 2025)
ObjectiveModerate Intensity Continuous Training (MICT) is recognized as an effective intervention for improving negative affect. However, research on its effects across varying levels of negative mood states in sedentary female college students remains limited. This study aimed to investigate the impact of a 12-week MICT intervention on different levels of negative mood in sedentary female college students.MethodsA total of 144 participants were randomly assigned to two groups, each consisting of 72 individuals. The participants were further categorized into three negative mood groups: depression, anxiety, and stress, with 24 participants in each group. Within each mood group, participants were divided into three subgroups based on the severity of their mood (mild, moderate, and severe), with 8 participants in each subgroup. The experiment spanned 12 weeks, with two 45-min training sessions per week. Intensity was monitored throughout the experiment using the Borg Rating of Perceived Exertion (RPE), and heart rate was measured immediately following each session. The training intensity was maintained at 60–69% of HRmax throughout the 12 weeks.ResultsAfter 12 weeks of MICT, MICT had a positive effect on mild and severe depressive mood, moderate anxiety, and mild stressful mood in sedentary female college students (p < 0.05), but MICT did not have statistically significant effects on moderate depressive mood, mild and severe anxiety, and moderate and severe stressful mood in sedentary female college students (p > 0.05).ConclusionMICT may have a beneficial effect on sedentary female college students, particularly those with lower levels of emotional distress. However, due to the absence of a positive control group, it is difficult to draw definitive conclusions about its specific impact. Future studies should employ more rigorous control designs to better assess the role of MICT in improving both the physical and mental health of sedentary female college students.